Pola Komunikasi yang digunakan Ibu terhadap Keberhasilan Anak dalam Melakukan Toilet Training - Dina Ramadhani; Oswati Hasanah; Rismadefi Woferst (HEALTH CARE: JURNAL KESEHATAN, 2023)
Introduction: Toilet training is a way to practice self-control, especially controlling urination and defecation. Toilet training is one of the developmental tasks when a child enters toddler, while independence in toilet training is achieved when the child is at preschool age. The achievement of toilet training is influenced by several factors, one of which is communication patterns. Communication patterns consist of functional communication patterns and dysfunctional communication patterns. This study aims to determine the relationship of the communication pattern used by the mother to the child's success in toilet training. Methods: This study used a descriptive correlative design with a cross sectional approach. The research sample was 97 respondents using purposive sampling technique. This study uses a questionnaire that has been tested for validity and reliability. The analysis used is univariate analysis and bivariate analysis. Results: the results of univariate analysis showed that the majority of children were at preschool age (37-48) months (61.9%), female gender (50.5%), parents' education was college (47.4%), people's occupations parents are housewives (49.5%). 55 respondents (56.7%). The results of this study also show that more than half of the respondents have a good/functional communication pattern (58,8%). The results of the bivariate analysis showed that there was a relationship between the mother's communication pattern and the child's success in toilet training for toddlers and preschool (p value 0.000; alpha 0.05%). Conclusion: Good/functional communication patterns affect children's success in toilet training. Keywords: Communication pattern, pre school, toddler, toilet training